2009
DOI: 10.1021/nn900401b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Structural, Magnetic, and Spintronic Characteristics of Sandwiched EunCOTn+1 (n = 1−4) Clusters

Abstract: Europium (Eu)-cyclootetatrene (COT = C(8)H(8)) multidecker clusters (Eu(n)COT(n+1), n = 1-4) are studied by relativistic density functional theory calculations. These clusters are found to be thermodynamically stable with freely rotatable COT rings, and their total magnetic moments (MMs) increase linearly along with the number of Eu atoms. Each Eu atom contributes about 7 mu(B) to the cluster. Meanwhile, the internal COT rings have little MM contribution while the external COT rings have about 1 mu(B) MM align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 36 publications
1
66
0
2
Order By: Relevance
“…To date, various organometallic sandwich clusters have been successfully synthesized experimentally and extensively explored theoretically. The possible metal elements include alkali (alkaline‐earth) metals, 3 d ‐transition metals (TM), 4(5) f ‐lanthanide (actinide) metals (Ln); and the organic ligand molecules can be different hydrocarbon cycles C n H n ( n = 3–8) . Particularly, in 1995, Kaya and Nakajima group have synthesized stable linearly multidecked vanadium n –benzene m (V n Bz m , Bz = benzene = C 6 H 6 ) complexes using laser vaporization technique .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, various organometallic sandwich clusters have been successfully synthesized experimentally and extensively explored theoretically. The possible metal elements include alkali (alkaline‐earth) metals, 3 d ‐transition metals (TM), 4(5) f ‐lanthanide (actinide) metals (Ln); and the organic ligand molecules can be different hydrocarbon cycles C n H n ( n = 3–8) . Particularly, in 1995, Kaya and Nakajima group have synthesized stable linearly multidecked vanadium n –benzene m (V n Bz m , Bz = benzene = C 6 H 6 ) complexes using laser vaporization technique .…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons that the metal‐ligand sandwich complexes becomes the hot research topic is their rich physical and chemical properties, which show great potential applications in catalysis, spintronics, optics, molecular recognition, biosensor, and so on. Generally, the metal atoms and ligand molecules form stable sandwich motifs via ionic‐covalent bonding and even pure ionic bonding . More interestingly, Stern–Gerlach magnetic deflection experiments have revealed linear size‐dependent magnetic moments of V n Bz n + 1 ( n = 1–4) clusters and ultrahigh magnetic moments of Eu n COT m (COT = C 8 H 8 = 1,3,5,7‐cyclooctatetraene) .…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental 3-8 and theoretical [9][10][11][12][13][14][15][16][17][18][19][20][21][22] works have reported that a wide variety of organic ligands are able to form stable multidecker sandwich clusters with suitable metals, such as TM-Bz (Bz = benzene, TM = Sc-Ni), 19 and Ln-COT (COT = cyclooctatetraene, Ln = Eu, Tb, Ho, Tm). 8 These clusters exhibit unusual magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…8 These clusters exhibit unusual magnetic properties. For example, the magnetic moment of V n Bz n+1 increases linearly along with the size; 13 Eu n COT n+1 possess extraordinarily high magnetic moments and high spin filter efficiency; 14,23 hybrid TM n (FeCp 2 ) n+1 clusters show significant magnetic moment enhancement as compared to their constituted monometallic counterparts. 15,21,24 In addition, many infinite 1D sandwich molecular wires exhibit exceptional high spin filter efficiency, which are important in the application of spintronics.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] The latter ligand has found widespreadu se in actinidea nd lanthanide chemistry. [12] For instance, the oxidationo fl anthanide sandwich complexes of the form Ln(COT'') 2 resultsi nt he formation of corresponding triple-decker complexes Ln 2 (COT'') 3 . [8] For the furtherd evelopment of this field, functionalized COT ligandshave played akey role.…”
Section: Introductionmentioning
confidence: 99%